INVIERTE.PE AND CLOSING GAPS IN THE CITY OF LAMBAYEQUE, PERU - Chapoñan Cuzo, Deybi Miguel (2023)
This study called "Invierte.pe and closure of gaps" aims to determine the impact of the new investment system for closing gaps in public services at the level of the province of Lambayeque, Peru. For this purpose, the 27th Non-experimental research, applied type, quantitative approach, and causal correlational level, with a target population of a census sample that was made up of 60 public servants who are in charge of managing investments at the Invierte.pe level twenty-one. In addition, the data collection strategy for said target population was used, which was determined by applying study techniques and instruments such as the questionnaire. To test the validity of For reliability, Cronbach's alpha was chosen, confirmed by the judgment of experts in the field, obtaining the value of the significance statistic = 0.000 < 0.05, rejecting the null hypothesis and accepting the alternative, that is, it has been determined 15 that the Management of Invierte.pe influences the Closing of Gaps in Public Services, in the Province of Lambayeque. Therefore, it is concluded that the impact levels are 56.8% according to the value of the R2 Nagelkerk according to the statistical results, achieving that this investment system directs the resources of investment projects more efficiently. on the other hand, the investments that have been channeled and respond to the prioritization of needs in the province, which have been programmed and planned, applying the technical criteria that correspond to public investment cycles.